High gain tapered slot antenna design and link budget analysis for inter-satellite link at 60GHz - Saisandeep, Banda; Rao Morla, Venkateshwara; Ahmadsaidulu, Shaik; S.L. Prasanna, Ch; Rao Tirumalasetty, Venkata; ., . (International Journal of Engineering and Technology, 2017)
The latest solution for Global Connectivity is Inter-satellite communication. Inter-satellite communication will able to connect two or more satellites directly and hence efficient data transfer is possible with less delay. Choice of frequency is key concern for inter-satellite communication. In this paper, precisely mentioned about importance of millimeter range frequency band for inter-satellite links (ISL) and more focused on the Tapered Slot antenna (TSA) design at 60 GHz. In the design, Substrate Integrated Waveguide SIW feed and corrugation techniques is used to achieve high gain and narrow beam width. Power Divider is used to design two-element TS antenna of 23 dB. For further outlook of antenna design link analysis is also calculated. Â Â